Suicide, self-injury, and violence in the schools : assessment, prevention, and intervention strategies - Juhnke, Gerald A.; Granello, Darcy Haag.; Granello, Paul F. (Hoboken, NJ : Wiley, 2010)
'The increasing rate of suicide, self-injury, and violence among adolescents in school settings has created a strong need for more information on these topics for professionals working in the field. This book is the first of its kind to provide school psychologists with information on assessing and preventing the risk of all three in a practical, concise, and affordable format. Counselors, psychologists, and social workers in school settings will benefit from this book's practical step-by-step methods for dealing with the risk of violence, self-injury, and suicide'--
'. This book will be the first of its kind to provide school's first responders (that is, school counselors, psychologists, social workers, teachers, and administrators) with information on assessing and preventing these risks in a practical, concise, and affordable format'--
Machine generated contents note: Chapter 1: Suicide in Children and Adolescents (with contributions by Karen Michelle Hunnicutt Hollenbaugh and Alexis M. Rae) -- Chapter 2: School-Based Suicide Prevention Programming -- Chapter 3: Working with Suicidal Students in Schools Assessment and Intervention -- Chapter 4: Working with Students who Engage in Non-Suicidal Self-Inflicted Injury (NSSI) -- Chapter 5: After a Suicide: Postvention in the School Environment -- Chapter 6: Utilizing Face-to-Face Clinical Interviews with Violent and Potentially Violent Students and Their Families -- Chapter 7: Using a Systems of Care Approach with Post Violent and Potentially Violent Students -- Chapter 8: Utilizing Psychological First Aid when Responding to School Violence Survivors and Their Parents -- Chapter 9: Adapted Solution Focused Survivors-Parents Debriefing Model -- Chapter 10: Ethical and Legal Issues -- Chapter 11: Wrap Up: Preparedness, Checklist Template, and Promising Future Interventions.
Includes bibliographical references (p. 347-356) and index.
Includes bibliographical references and index.
Keywords: Students -- Suicidal behavior; Adolescent psychology; Suicide -- Prevention; School violence -- Prevention; Violence in children -- Prevention; Violence in adolescence -- Prevention; Educational counseling; School psychology